Trophic niche changes associated with the eradication of invasive mammals in an insular lizard: an assessment using isotopes - Ferreira Nunes, Sara (2021)
Invasive species are a major threat to island biodiversity, and their eradications have substantially contributed to the conservation of island endemics. However, the consequences of eradications on the trophic ecology of native taxa are largely unexplored. Here, we used the eradication of invasive black rats Rattus rattus and European rabbits Oryctolagus cuniculus from the Berlenga Island, in the western coast of Portugal, as a whole-ecosystem experiment to investigate the effects of the eradication of invasive mammals on the trophic niche and body dimensions of the island-restricted Berlenga wall lizard Podarcis carbonelli berlengensis over a 2-year period. Our results suggest an expansion of the isotopic niche and an intensification of the sexual dimorphism of the lizard following mammal eradication. Additionally, we found considerable variability in isotopic niche across the island and detected evidence of sex-specific and season-modulated nutritional requirements of this threatened reptile. Our findings support that the eradication of 2 of the planets most problematic invasive vertebrates led to changes in the lizard trophic niche and sexual dimorphism in just 2 years. This suggests that the ecological pressuresfor example, prey availability and habitat structureto which lizards are exposed have substantially changed post-eradication. Our study emphasizes the scientific value of island eradications as experiments to address a wide range of ecological questions and adds to the increasing body of evidence supporting substantial conservation gains associated with these restoration interventions.